The Effect of Pop-Up Advertising and Perceived Intrusiveness on Brand Awareness and Advertising Avoidance With Advertising Value As A Moderation Factor : (Study on Youtube Users) - gana bisatya, sanggya; Sukresna, I Made (International Journal of Scientific Research and Management (IJSRM), 2022)
The high usage statistics for Youtube make this social media used by companies for advertising. But society has a different attitude in dealing with online advertising. This research aims (1) to analyze the effect of pop-up ads on perceived intrusiveness; (2) to analyze the influence of perceived intrusiveness on brand awareness; (3) to analyze the effect of perceived intrusiveness on advertisement avoidance; and (4) to analyze the role of advertising value in moderating the influence between perceived intrusiveness and avoidance of advertising. This study is a conclusive quantitative study with 120 respondents.The results of the study found that the more pop-up ads that were considered annoying, causing feelings of annoyance, and the ads were avoided, the higher the level of disturbance felt by respondents (Youtube viewers), the greater the opportunity to avoid ads that appeared, the more disturbances felt, the will attract more attention and web advertising content has a greater chance to be easily remembered by the audience, the value of the advertisement is able to reduce a person's chances of avoiding advertisements for the perceived distraction with the advertisement itself.